Masculinities at the Crossroads: Theoretical Insights into Gendered Violence and Social Class in Taslima Nasrin's Lajja - Chakraborty, Sanjana; Tripathi, Dhananjay (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
The present article critically examines the intricate tapestry of gendered space within Taslima Nasrin’s Lajja (2014). It aims to unravel the social positionality of men within minority communities in conflict scenarios. Primarily based on the theories of Susan Bordo, Michael Kimmel, and Raewyn Connell, among others, the paper underscores the complexities surrounding gendered violence and the formation of male identity. It highlights the emergence of subaltern masculinity, layered with the embodied realities of masculinity. This fosters a sense of “otherness” among men belonging to minority groups. It furthers the psychological and physical trauma borne by male bodies in the discourse of gender-based violence. This paper delves into the intricate intersections of racial and ethnic identities within social class dynamics, unraveling the multifaceted expressions of masculinity within diverse communities. Through a lens focused on gendered violence, I explore the unique challenges and experiences faced by men navigating the complex terrain of multiple intersecting identity factors. The research probes into the systematic invisibility of victims who identify as men on the gender spectrum, juxtaposed with their unjust association with the image of the perpetrator. In essence, this study contributes to the theoretical discourse surrounding the connections between masculinities and social class, unraveling the multifaceted layers of gendered violence against men within the unique socio-cultural context depicted in Lajja.